Tuberculosis and Pregnancy - Osma Sala, Ernesto (2015)
It has conducted a study of 597 cases of patients with pulmonary tuberculosis and pregnancy, predominantly advanced and chronic pulmonary disease evolution in 48.9%. Of all patients, 63% were hospitalized in the last months of pregnancy. The tuberculostatic therapy was instituted in all cases currently in use; pregnancy monitoring was conducted by the obstetrician. Nevertheless, reactivations or postpartum lesion extensions have only reached 2%. Dystocia occurred in 4.4% of cases, almost all by obstetric cause; Two patients, cardio-respiratory failure sued caesarean section. Three patients died from pulmonary expansion process, one of which entered into labor in marked respiratory failure due to extensive lesion and severe, complicated with unilateral pulmonary drilling quality. The overall average weight of children at birth showed trends in general, to be lower in the children of mothers with moderately advanced in advanced pulmonary forms. The pathological study revealed tuberculous lesion placenta not in any case; the cultivation of this material was positive in six samples, five of them only one or two colonies. The amniotic fluid was positive for B. K. as cases; three colonies only one or two. Doubt about the necessary aseptic receipt of samples allowed to issue final judgment on the matter; the fourth case corresponded to that of a child who died two months after giving birth in another hospital with generalized tuberculosis.